Actas del Coloquio Internacional Sobre el pensamiento de Merleau-Ponty - Solas, Silvia (Comp.) (Trabajos, comunicaciones y conferencias, 2018)
The works gathered here reflect the result of the communications and conferences presented at the Coloquio Internacional Sobre el pensamiento de Maurice Merleau-Ponty held on December 6 and 7, 2016 at the FaHCE-UNLP.